Curvas-chaves da seção de uma microbacia hidrográfica na região amazônica - Simioni, Cássio Fernando (2020)
Many microbasins lack information that relationship the use and occupation of soil with the quality and availability of surface water. The acquisition of this data facilitates the work of managing water resources, so that the use of water for a given purpose does not harm other possible uses. Thus, the objective of the present study was to evaluate the flow rate and the transport of sediments in the fluviometric section of the Caiabi river microbasin, in order to define its rating curves, from measurements of the water level, river flow, suspended sediment and bed-load sediment. The flow rating curves achieved very good adjustments for the power models, however, monitoring extreme values was decisive in choosing the most appropriate curve for the section. The statistical performance of the rating curves of the solid discharge indicated that the best representation of the sediment flow in the section is obtained through the association between suspended sediment and bed sediments samples. Among the proposed models, the exponential was chosen because offering the best fit the observed solid discharges.